Optimizing Preventive Maintenance to Reduce Downtime On CAT KT4 Axle Loader Components in The Mining Industry - Dewa Hadi Prasetyo; Febi Rahmadianto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Damage to rotable axle components on CAT KT4 Loaders in the mining industry is often the main cause of operational downtime. This study aims to analyze the frequency of damage to axle components and evaluate the effectiveness of preventive maintenance to reduce downtime duration and repair costs. Damage data collected from January to August 2024 were quantitatively analyzed to identify the most frequent damage patterns, especially seal leaks and brake modules. The results show that the implementation of preventive maintenance, such as regular seal replacement and hydraulic pressure checking, can significantly reduce the frequency of breakdowns and improve operational efficiency. The research also provides recommendations on maintenance strategies that can be implemented to extend component life and reduce overall downtime.